2011
DOI: 10.1007/s12205-011-1009-z
|View full text |Cite
|
Sign up to set email alerts
|

A displacement-based seismic design for reinforced concrete structures

Abstract: The Displacement-Based Design method is presented for linear and non linear systems with some numerical applications on one storey and multistory buildings using the spectra and formulae provided by the Algerian seismic code. Fundamentals and design procedure of this method are given with implications and inherent problems. A brief review of the classic (force-based) method is also given. Comparison between the two methods is made and the limits and advantages of each one are discussed. Furthermore, the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The aforementioned scholars have studied and discussed the application of the method to members, and in terms of different types of structural systems, Yang and Lu 27 proposed a direct displacement design method based on the concept of inelastic design spectrum for prestressed concrete shear walls and verified the applicability of the method by design examples. Boulaouad and Amour 28 used the displacement‐based design method to simulate single‐ and multi‐story buildings numerically, gave the basic principles and design steps of the method, and compared it with the force‐based method. The analysis results showed that the displacement‐based method is simple, efficient, and has sufficient accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned scholars have studied and discussed the application of the method to members, and in terms of different types of structural systems, Yang and Lu 27 proposed a direct displacement design method based on the concept of inelastic design spectrum for prestressed concrete shear walls and verified the applicability of the method by design examples. Boulaouad and Amour 28 used the displacement‐based design method to simulate single‐ and multi‐story buildings numerically, gave the basic principles and design steps of the method, and compared it with the force‐based method. The analysis results showed that the displacement‐based method is simple, efficient, and has sufficient accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its complexity, this procedure is used only for special cases. For current use, in order to meet the requirements for the several limit states provided by the different codes, a number of simpler design procedures were recently developed and jointly termed "Performance Based Seismic Design" (Boulaouad and Amour, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wallace (1995a and1995b) presented new code format for seismic design of RC structural walls, a performance design methodology relative to concrete structural walls was proposed by Sasani (1998). Boulaouad and Amour (2011) presented a displacement-based seismic design method for reinforced concrete structures. Kowalsky (2001) presented RC structural walls designed according to the UBC and displacement-based methods.…”
Section: Introductionmentioning
confidence: 99%